Forming student character through clean and healthy life behavior in schools - Vina Oktiarina; Sri Wahyuni; Etty Nurkhayati; Mulki Siti Hajar Rezaini; Budi Nur Yudhistira (Journal of Advanced Research in Social Sciences and Humanities, 2022)
Aim: Everyone in the school community, including students, teachers, and parents, has a role in promoting a healthy environment. Students are expected to acquire the background they need to advocate for healthy lifestyle choices and independently implement preventative measures against illness. Schools can only succeed with UKS (School Health Business) initiatives that promote healthy eating and exercise as part of a broader focus on promoting positive health behavior among students. This paper aims to shed light on the significance of school health efforts in inspiring students to form and keep up with lifestyle choices that are good for their own and the community’s health. Methodology: In the context of the secondary school system in Serang City, a total of 300 participants were analyzed by regression analysis. Findings: Students who took part in school health efforts were found to be more likely to adopt healthier behaviors. There are many benefits to promoting education on healthy and clean lifestyles in schools, including broadening teachers’ horizons, increasing teachers’ motivation and output at work, and reducing tension in teachers’ interactions with their students. Implications/Novel Contribution: This study will provide light on the significance of health education programs in schools and how they affect healthy lives and the formation of strong moral character.